Manajemen Diagnosis Kesulitan Belajar di SMPN 1 Langkaplancar - Pajrin Nurlina; Elita Putri Melati Endi heryadi; Apit Apit (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2024)
The diagnostic management of learning difficulties can be understood as an effort to manage or control the difficulties experienced by students in order to achieve maximum possible results in achieving previously agreed goals. The learning difficulties examined in this research are only limited to the diagnostic management of learning difficulties, especially students' difficulties in achieving learning outcomes or abilities, in this case students have intelligence that is not below average but have poor learning abilities. This research aims to determine the management of the diagnosis of learning difficulties experienced by students at SMPN 1 Langkaplancar as well as the causes and appropriate treatment methods for the difficulties faced. The subjects of this research were instructors or supervising teachers and students of SMPN 1 Langkaplancar. The results of research in the field show that there are many factors that cause learning difficulties, one of which is that the material is given in a monotonous way, which has an impact on not maximizing absorption and focus management which results in learning difficulties for students.